Evaluation the Antimicrobial Effect of Glycerin Magnesia on Some Bacteria, In-Vitro Study - Maher Saber Owain1 , Khalid Ismael Oleiwi2 , Ali Ghazi Atiyah1 , Mustafa Salah Hasan2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
This study was aimed to assess the efficacy of glycerin magnesia on some bacteria. A thirty percent of glycerinmagnesia were prepared as explained below. Many types of bacteria including Proteus spp., Staphylococcusaureus, Staphylococcus epidermidis, Acinetobacter, E. coli, Pseudomonas aeruginosa, Salmonella spp. wereselected for this study and obtained from university of Tikrit, college of veterinary medicine. A bacterial brothwere prepared, a then a sterile swab were emulsify in these broth and streaked on muller hinton agar plateand allowed till dry, then a holes were filled with a given glycerin magnesia and incubated for 24hrs. at 37?C. The results showed that a higher antibacterial effects of glycerin magnesia against Staphylococcus aureusfollowed by Proteus spp., Pseudomonas aeruginosa, Salmonella spp., Acinitobacter, E. coli, Staphylococcusepidermidis respectively.In conclusion, the glycerin magnesia have a wide range antibacterial effect and can be used in future inwound healing.